Mathematical demography of the Cape vulture - Piper, Steven Edward (Department of Mathematics and Applied Mathematics, 2016)
The Cape Vulture Gyps coprotheres is one of the world's largest avian scavengers and was once widely distributed in southern Africa, to which it is endemic. It has suffered major changes of fortune in recorded history and has, at least twice, undergone large range contractions and expansions in the Cape Province. It has variously been classified as 'rare', 'vulnerable' or 'threatened'. It is currently thought, by some, to be in decline. The central aim of these researches is to answer the 'Grand Question': What is the probability that the Cape Vulture will survive well into the twenty-first century as a free-flying bird? This is followed by a secondary question: What is the stability of the population in space, time and age-structure?